Predicting Firm Value in The Jakarta Islamic Index with Profitability as A Mediating Variable - Winarsih Winarsih; Khoirul Fuad (Jurnal Kajian Akuntansi, 2022)
AbstractThe purpose of this study is to analyze and empirically examine profitability in predicting a firm value in the sector of companies listed on the Jakarta Islamic Index (JII). The research sample consisted of 40 annual reports of sector companies listed on the Jakarta Islamic Index from 2017 to 2019, which were analyzed using AMOS software. This study found that Intellectual Capital positively affects firm value, but Management Statement Disclosure and Corporate Social Responsibility are not proven to affect firm value. Furthermore, profitability mediates the relationship between intellectual capital, Corporate Social Responsibility, and Management Statement Disclosure on firm value.Keywords: Corporate social responsibility; Firm value; Intellectual capital; Management statement; ProfitabilityAbstrakArtikel ini bertujuan untuk menganalisis dan menguji secara empiris profitabilitas dalam memprediksi nilai perusahaan pada sector perusahaan yang terdaftar di Jakarta Islamic Index. Sampel penelitian terdiri dari 40 laporan tahunan perusahaan sektor yang terdaftar di Jakarta Islamic Index dari tahun 2017-2019, yang dianalisis dengan menggunakan software AMOS. Hasil penelitian menunjukkan bahwa Intellectual Capital berpengaruh positif terhadap nilai perusahaan, tetapi Management Statement Disclosure dan Corporate Social Responsibility tidak terbukti berpengaruh terhadap nilai perusahaan. Hasil analisis meunjukkan bahwa profitabilitas terbukti memediasi pengaruh Management Statement Disclosure, Intellectual Capital dan Corporate Social Responsibility terhadap nilai perusahaan.Kata kunci: Corporate social responsibility; Intellectual capital; Management statement; Nilai perusahaan; Profitabilitas